Spiritualitas Gembala (Satua Niha Keriso) dalam Perspektif Perjanjian Baru dan Implikasi Keteladanan dalam Pembinaan Jemaat (Jurnal Pendidikan Agama dan Teologi, 2025)
The spirituality of shepherding (Satua Niha Keriso) plays a crucial role in shaping spiritual leadership within the congregation. This article examines the concept of shepherding from a New Testament perspective and its implications for church development. Using a qualitative approach based on biblical and theological studies, this research highlights Christ’s example as the Good Shepherd and its application in church ministry. The findings indicate that the spirituality of shepherding is not only related to teaching and faith nurturing but also reflects love, humility, and responsibility in building a spiritually healthy community. These findings emphasize that church leaders must embody the values of true shepherding in nurturing, guiding, and serving their congregation with integrity. Thus, the spirituality of shepherding contributes to strengthening faith and fostering church growth in the contemporary context.